2001
DOI: 10.1046/j.1365-8711.2001.04513.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase models for the evolved planetary nebulae NGC 6781, M4-9 and NGC 7293

Abstract: We have studied the chemistry of the molecular gas in evolved planetary nebulae. Three pseudo‐time‐dependent gas‐phase models have been constructed for dense (104–105 cm−3) and cool (T∼15 K) clumpy envelopes of the evolved nebulae NGC 6781, M4‐9 and NGC 7293. The three nebulae are modelled as carbon‐rich stars evolved from the asymptotic giant branch to the late planetary nebula phase. The clumpy neutral envelopes are subjected to ultraviolet radiation from the central star and X‐rays that enhance the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
(17 reference statements)
6
26
0
Order By: Relevance
“…The CN/HCN ratio calculated by Hasegawa et al (2000) is in the range 1.4 to 6.6, depending on the volume hydrogen density and the kinetic temperature, in good agreement with our average value (∼2.6). The abundances of HCN and HNC calculated by Ali et al (2001) are in general agreement with the observations reported here. However their abundance of CN is too high by a factor of ∼3.…”
Section: Chemistry Of N-bearing Moleculessupporting
confidence: 90%
See 4 more Smart Citations
“…The CN/HCN ratio calculated by Hasegawa et al (2000) is in the range 1.4 to 6.6, depending on the volume hydrogen density and the kinetic temperature, in good agreement with our average value (∼2.6). The abundances of HCN and HNC calculated by Ali et al (2001) are in general agreement with the observations reported here. However their abundance of CN is too high by a factor of ∼3.…”
Section: Chemistry Of N-bearing Moleculessupporting
confidence: 90%
“…Nevertheless, this ratio seems again to be relatively lower in the two youngest objects (HNC/HCN < ∼ 0.2) than in some more evolved ones (HNC/HCN up to ∼1). These values are in the range of those previously observed in other nebulae (Bachiller et al 1997a) and estimated theoretically (Ali et al 2001).…”
Section: Column Densities and Their Evolutionsupporting
confidence: 89%
See 3 more Smart Citations